La necesidad de garantizar los derechos constitucionales, de las personas vulnerables, como; niños, niñas y adolescentes, personas de la tercera edad, y discapacitados que trabajan en el sector no remunerado. por medio de reformas al código de trabajo. - García Cáceres, Jaime Bolívar (2015)
The rights of vulnerable people, such as; children and adolescents, the elderly, disabled and working in the unpaid sector. They are not guaranteed a technical way in which social security is the reason why it is necessary for the state I imposed policies to achieve these objectives. The Constitution of the Republic of Ecuador guarantees the right of individuals; disabled, the elderly, women, boys / girls and adolescents towards work and performance, but not Regalia unpaid work that is done domestic. The rights of all workers are inalienable, and indefeasible intangibles therefore must be met not only by the state but within the family and social circle, in order to safeguard their rights the state must establish legal guidelines for this sector. Fundamental rights must be satisfied, since our state guarantees social protection in all orders, so the lack of guidelines and protected are mechanisms to vulnerable and priority sector and their rights and guarantees established in the Constitution and international instruments, of which our state is signature